Respuesta :

9514 1404 393

Answer:

  • (5, -1)
  • (3, 1)
  • (0, 4)

Step-by-step explanation:

Apparently, you are supposed to assume that ...

  y = g(x)

  y = 4 - x

For the one given value of x, the corresponding y value is ...

  y = 4 - 3 = 1

So, for that x-value, the table entry is (x, y) = (3, 1).

__

To find the missing x-values, you can solve the equation for x.

  y = 4 - x

  x + y = 4 . . . . add x

  x = 4 - y . . . .  subtract y

Now, for the given y-values, we can find the corresponding x:

  x = 4 -(-1) = 5   ⇒   (x, y) = (5, -1)

  x = 4 -(4) = 0   ⇒   (x, y) = (0, 4)

So, your table will be ...

Ver imagen sqdancefan
ACCESS MORE